Genetics or Environment: Tracing the Root Cause of Increasing Homosexual Population - Pimentel, Jonald; Garcia, Anna Jean S. (Advances in Social Sciences Research Journal, 2022)
The number of homosexuals at present is enormously increasing in the Philippines. These homosexuals established themselves in the academe, government, services, industry and in the private sectors. They contributed a lot in the society shaping government policies where they were given attention especially in their demands of acceptance and equality. However, some homosexuals are also contributing the spread of disease particularly HIV-AIDS due to their sexual practices and activities. The increase of this group of individuals causes a distortion on the growth of human population since they do not produce offspring due to same sex partnership. This study investigated the root cause of homosexuality and the link of these homosexual’s sexual orientation and behavior with its family influences, environment, exposure to violence and childhood experiences. It has been a long debate known as nature-nurture debate whether homosexuality is caused by genetics or environment. Using a constructed validated questionnaire, four hundred fifty-five persons that have tendencies to be homosexuals were selected and their responses were gathered. Describing their sexual orientations, out of the total 455 individuals, 56 (12.3%) were straight males and 88 (19.34%) were straight females, 96 (21.09%) admitted to be bisexual, 123 (27.03%) were gays and 91 (20%) were lesbians. The results of data analysis using Chi-square test, showed that there was a significant association between the sexual orientation and the birth order as well as an individual having a homosexual sibling and history of childhood abuse.